2021
DOI: 10.1155/2021/5561272
|View full text |Cite
|
Sign up to set email alerts
|

Xinkeshu Improves Endothelial Function and Augments Reendothelialization Capacity in Coronary Artery Disease with Anxiety/Depression

Abstract: The disruption of endothelial homeostasis is the hallmark of coronary artery disease (CAD) and psychological disorders such as anxiety/depression. Xinkeshu (XKS), a traditional Chinese patent medicine, plays an essential role in CAD and psychological condition; however, the mechanisms underlying the effects of XKS on the endothelial function and endogenous endothelium-repair capacity in CAD patients with anxiety/depression remain elusive. In this study, endothelial function and endothelial progenitor cell- (EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Specific mixtures of herbs, notably Ge Gen Baicalin Wan and Sheng Wei San, possess the capacity to impart vasoprotective effects by orchestrating the modulation of distinct signaling cascades, including the HMGB1/NF-κB/NLRP3 and ROCK/cofilin pathways ( 103 , 104 ). Additionally, Xinkeshu, through its enhancement of endothelial progenitor cell-facilitated endothelial regeneration, and rhodopsin, by modulating the hepatic low-density lipoprotein receptor (LDLR) and endothelial nitric oxide synthase (p-eNOS), potentially contribute positively to the improvement of endothelial functionality ( 105 , 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specific mixtures of herbs, notably Ge Gen Baicalin Wan and Sheng Wei San, possess the capacity to impart vasoprotective effects by orchestrating the modulation of distinct signaling cascades, including the HMGB1/NF-κB/NLRP3 and ROCK/cofilin pathways ( 103 , 104 ). Additionally, Xinkeshu, through its enhancement of endothelial progenitor cell-facilitated endothelial regeneration, and rhodopsin, by modulating the hepatic low-density lipoprotein receptor (LDLR) and endothelial nitric oxide synthase (p-eNOS), potentially contribute positively to the improvement of endothelial functionality ( 105 , 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, current guidelines recommend non-psychotropic drug intervention as the initial treatment [19]. Yet, numerous clinical and experimental studies have confirmed that Traditional Chinese medicine (TCM) has a definite effect and relatively high safety in the treatment of psycho-cardiology disease [20][21][22][23]. Qi-Shao-Tong-Mai-An-Shen (QSTMAS) herbal paste, summarized by Professor Huang Li based on 40 years of clinical experience, is used to treat CHD with qi deficiency and blood stasis symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, current guidelines recommend non-psychotropic drug intervention as the initial treatment [19]. Yet, numerous clinical and experimental studies have con rmed that Traditional Chinese medicine (TCM) has a de nite effect and relatively high safety in the treatment of psycho-cardiology disease [20][21][22][23]. QSTMAS herbal paste, one Chinese patent preparation summarized by Professor Huang Li based on 40 years of clinical experience, is used to treat coronary heart disease with qi de ciency and blood stasis symptoms.…”
mentioning
confidence: 99%